A homozygous PRKN-associated juvenile Parkinson's disease with pregnancy in China - Li, Hong-xing; Dong, Mei; Peng, Xiao-xiao; Liu, Yi-zhe; Wang, Han; Li, Chao; Du, Yi-yi; Zhang, Kai; Zong, Qiang (Frontiers in Neurology, 2023)
Background Although Parkinson's disease (PD) is the second most common neurodegenerative disorder, pregnancy in patients with PD is a relatively rare occurrence because the most common age of onset of PD is beyond the childbearing age, except in patients with Young-Onset PD (YOPD) caused by parkin RBR E3 ubiquitin protein ligase (PRKN) mutations. Case In this study, we report the case of a 30-year-old Chinese woman who was affected by PRKN-associated YOPD and was treated with levodopa/benserazide during pregnancy. She gave birth to a healthy baby boy with an Apgar score of 9 through an uncomplicated vaginal delivery. Conclusion This case further suggests that levodopa/benserazide during pregnancy is safe in the treatment of PRKN-associated YOPD.